Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s00464-008-9799-x
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic esophageal mobilization during minimally invasive esophagectomy: a head-to-head comparison of prone versus decubitus positions

Abstract: Prone thoracoscopic esophageal mobilization appears to be equivalent to decubitus thoracoscopic esophageal mobilization with respect to blood loss, number of lymph nodes dissected, and complications, but with a significant reduction in thoracoscopic surgical time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
87
4
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 11 publications
6
87
4
4
Order By: Relevance
“…Fabian et al indicated the results of prone positioning to be equivalent to lateral decubitus in terms of blood loss, lymph node dissection, and complications and reported significantly shorter operative duration in prone position. The authors concluded that conversion to open thoracotomy may be easier in lateral position (11). But, the previous studies did not give any preference to any of the two methods (3).…”
Section: Discussionmentioning
confidence: 97%
“…Fabian et al indicated the results of prone positioning to be equivalent to lateral decubitus in terms of blood loss, lymph node dissection, and complications and reported significantly shorter operative duration in prone position. The authors concluded that conversion to open thoracotomy may be easier in lateral position (11). But, the previous studies did not give any preference to any of the two methods (3).…”
Section: Discussionmentioning
confidence: 97%
“…Prone positioning during thoracoscopic or robotic mobilization of the esophagus provides several advantages to the surgeon over the lateral decubitus position [1][2][3]. Prone positioning allows gravity to provide optimal exposure of the esophagus, and thus superb surgical view, because the lung falls away with minimal handling [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Prone positioning allows gravity to provide optimal exposure of the esophagus, and thus superb surgical view, because the lung falls away with minimal handling [1][2][3]. When assuring free abdominal and chest movements, the prone position does not significantly affect the respiratory system compliance and hemodynamics and improves oxygenation during general anesthesia [6,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47) This longer time is unlikely due to the increased difficulty of and unfamiliarity with positioning patients in the prone position. On the contrary, Fabian, et al 48) and Feng, et al 49) showed that the thoracoscopic procedure is performed significantly more quickly in the prone position. Since the number of procedures performed per institution is relatively small, data directly comparing PP to the LDP technique are particularly sparse.…”
Section: Surgical Outcomes Of the Prone Proceduresmentioning
confidence: 99%